Sustained improvement in patient‐reported outcomes during long‐term fesoterodine treatment for overactive bladder symptoms: pooled analysis of two open‐label extension studies - Kelleher, Con J.; Dmochowski, Roger R.; Berriman, Sandra; Kopp, Zoe S.; Carlsson, Martin (BJU international, 2012)
Study Type – Outcomes (cohort) Level of Evidence 2b What's known on the subject? and What does the study add? Short‐term (12‐week) trials have demonstrated that subjects with OAB who receive treatment with fesoterodine 4‐ and 8‐mg, either in fixed‐dose or flexible‐dose regimens, show significant improvements in measures of HRQL and other patient‐reported outcomes. The results of this long‐term, open‐label study show that treatment with fesoterodine for up to 24 months resulted in sustained improvement in measures of HRQL and severity of bladder‐related problems in subjects with OAB symptoms. Throughout the study, a high percentage of subjects reported satisfaction with fesoterodine treatment. The results were similar in men and women and across age groups (<45 years; 45–64 years; 65–74; ≥75 years). Long term treatment with fesoterodine is beneficial to patients with overactive bladder. OBJECTIVES • To evaluate the effects of long‐term fesoterodine treatment on health‐related quality of life (HRQL) and treatment satisfaction in subjects with overactive bladder (OAB) symptoms. • To determine the impact of gender and age on these effects. PATIENTS AND METHODS • This is a post hoc analysis of data pooled from identically designed open‐label extensions of two randomized, double‐blind, 12‐week fesoterodine studies. • Initial treatment was once‐daily fesoterodine 8 mg; subjects had the opportunity to receive open‐label fesoterodine for ≥24 months. • After 1 month, subjects could elect dose reduction to 4 mg and subsequent re‐escalation to 8 mg; dose reduction and re‐escalation were each allowed once annually. • Changes in scores on the King's Health Questionnaire (KHQ), International Consultation on Incontinence Questionnaire–Short Form (ICIQ‐SF) and a Likert scale evaluating severity of bladder‐related problems were assessed at open‐label baseline and months 12 and 24; treatment satisfaction was assessed at open‐label baseline and at months 4, 12 and 24. RESULTS • A total of 864 enrolled subjects were included (men, n= 182; women, n= 682; aged <45 years, n= 134; 45–64 years, n= 432; 65–74 years, n= 204; ≥75 years, n= 94); most subjects (77%) who continued treatment maintained the 8‐mg dose. • Among subjects in the overall population, there were significant improvements in all KHQ domains, ICIQ‐SF scores, and bladder‐related problems at open‐label baseline vs double‐blind baseline (P < 0.05); additional significant improvements were observed at months 12 and 24 vs open‐label baseline in all outcomes (P < 0.05) except for the KHQ General Health Perception domain. • When data were stratified by gender or age, significant improvements at open‐label baseline vs double‐blind baseline were further significantly enhanced or sustained at months 12 and 24 for most KHQ domains, and for ICIQ‐SF scores and bladder‐related problems for all groups. Women had significantly greater improvements than men in the KHQ Emotion (P= 0.0173) and Severity/Coping (P= 0.0112) domains and ICIQ‐SF scores (P= 0.0276) during open‐label treatment. Subjects aged <45 years had significantly greater improvement in the Personal Relationships domain compared with those aged 45–64 years (P= 0.0357) and in the Sleep/Energy domain compared with all other groups (all P < 0.02). • Treatment satisfaction was high (≥92%) throughout open‐label treatment regardless of gender or age. CONCLUSIONS • Long‐term fesoterodine treatment was associated with sustained improvement in measures of health‐related quality of life and bladder‐related problems and with high treatment satisfaction in subjects with overactive bladder symptoms. • Effects of gender and age were minimal.